Meta-Analysis: Risk Factors Associated with Multidrugs-Resistant Tuberculosis (MDR-TB) in Tuberculosis Patients - Nurul Dwi Andriani; Resta Dwi Yuliani (Journal of Health Promotion and Behavior, 2021)
Background: Today, the world not only has to face a higher number of deaths from TB every year, but other challenges arise in the form of drug-resistant TB with risk factors that can affect the incidence of MDR TB, namely treatment-related factors (direct) and other factors (not direct). direct) such as biological, social, economic, and health system factors. The aim of this study was to estimate the risk of HIV infection, smoking and previous medication history on the incidence of MDR TB, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study was conducted using a systematic review and meta-analysis study design using PICO, population: Tuberculosis Patients. Intervention: Risk Factors for HIV Infection, Smoking, and History of Medication. Comparison: no HIV infection, no smoking and no history of medication, Outcome: MDR-TB incidence. The articles used in this study came from 4 databases, namely Pubmed, ScienceDirect, ProQuest and Google scholar. The article keywords are ("Risk factor" or "associated") AND ("Multidrug resistant Tuberculosis" or "MDR TB") AND “Case Control” AND (HIV or Smoke or treatment). The articles included in this study are full paper articles, case-control study designs, 2011-2021 and the size of the relationship between Adj Odds Ratio. Article selection is done using PRISMA. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 20 case-control studies with 18,790 TB patients with details of 4,220 cases and 14,570 controls from 3 America, Africa, and Asia. HIV infection had a risk of 2.05 times in TB patients becoming MDR-TB (aOR = 2.05; 95% CI = 1.03 to 4.07; p= 0.040). Smoking had a 2.2 times risk in TB patients for MDR-TB (aOR= 2.20; 95% CI= 1.87 to 2.59; p<0.001). History of TB treatment had a 9.08 times risk in TB patients to become MDR-TB (aOR=9.08; 95% CI= 5.49 to 15.03; p<0.001).Conclusion: Risk factors for HIV infection, smoking and history of TB treatment increase the incidence of TB to MDR-TB.Keywords: Multidrugs Resistant Tuberculosis, HIV, smoking, TB treatment historyCorrespondence:Nurul Dwi Andriani. Public Health Science, Faculty of Public Health, Universitas Diponegoro, Central Java, Indonesia. Jl. Prof. Sudarto No.13, Tembalang, Semarang, Central Java. Email: nurul.d.andriani@gmail.com. Mobile: +6282137279586Journal of Health Promotion and Behavior (2021), 06(03): 233-249DOI: https://doi.org/10.26911/thejhpb.2021.06.03.07